Risk factors influencing humanitarian operations: a case of temple cart festival - S, Jeevan; Suresh, M; Ranganathan, Rajkumar (International Journal of Engineering and Technology, 2018)
The traditional Indian beliefs are concentrated on the strong holy force of positive vibration inside the temples and also during special occa-sions. Hence the human population gathering during the special occasions is uncontrollable. To control and manage the population, effective humanitarian operations are required and hence a framework is also required. In this paper, the objective is finding the risk factors influenc-ing on humanitarian operations in temple cart festivals and analyzing these factors. In order to study this, Interpretive Structural Modelling (ISM) approach is used to analyse the relationship among the risk factors of humanitarian operations. For the case study purpose, the data has been collected from the selected temple cart festival organizers in India. The paper projects forwards the most influential factors of oc-currence, detectability, disaster, preparedness which influences the humanitarian operations.Â Â